Pendampingan dan Peningkatan Kualitas Pengelolaan Administrasi Keuangan pada Usaha Industri Kecil Menengah “Tau Hinje” di Kelurahan Kereng Bangkirai: Assistance and Improvement of the Quality of Financial Administration Management in Small and Medium Industries "Tau Hinje" in Kereng Bangkirai Village - Ariyadi, Ariyadi; Jariah, Ainun; Sari, Mita; Sutrisno, Edi; Hidayat, Nanang (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Financial administration management is an important aspect of maintaining the continuity of micro and small businesses. So in seeing the development in the business carried out, orderly financial recording is needed. With accurate and regular financial records, business owners can more easily analyze financial performance and make more appropriate decisions to optimize profitability in business growth. With a better understanding of financial management, business actors can improve their competitiveness and make a greater contribution to the local economy. Thus, efforts to assist and improve the quality of financial administration management are strategic steps to support the development and progress of micro and small businesses in Kereng Bangkirai Village. The purpose of this activity is to improve the quality of financial administration management in small and micro enterprises in Kereng Bangkirai Village. In the context of outstanding students, this activity can be a forum for students to develop competencies and skills in the field of financial administration and community service. As part of the main performance indicators, this activity can be directed to achieve improvements in terms of the quality of financial administration management in small and micro enterprises in Kereng Bangkirai Village, such as increased revenue, operational efficiency, or compliance with tax and financial regulations. In the context of community service, this activity can provide direct benefits to micro and small business owners in Kereng Bangkirai Village by providing assistance and training to improve their financial administration management, so that it can be expected to help improve their economic welfare.